Controlling the Emergence and Shift Direction of Mechanochromic Luminescence Color of a Pyridine‐Terminated Compound. Issue 3 (17th January 2019) - Kondo, Mizuho; Yamoto, Taku; Miura, Seiya; Hashimoto, Mayuko; Kitamura, Chitoshi; Kawatsuki, Nobuhiro
Abstract: In this study, mechanochromic luminescence was induced in a complex of mechano‐inactive compounds. Dye/acid complexes containing the same π‐conjugated backbones were prepared. While the luminophore showed blue and red shifts in photoluminescence spectra when combined with different acids by grinding, it exhibited slight mechanoresponsiveness itself. Also, compounds with similar molecular backbones to the dye/acid complex were synthesized to clarify the color change mechanism. The compounds showed both blue and red shifts in photoluminescence and diffuse reflectance spectra upon grinding, indicating that mechanochromic luminescence in the hydrogen‐bonded complex is like its monomeric analogue and that aggregation structure plays an important role in mechanoresponsive behavior rather than the π‐conjugated structure. It was shown that a color change can be mechanically induced by imitating the solid‐state aggregation structure of other mechanoresponsive compounds without synthetic modification. Abstract : A colorful painting : What is necessary for mechanoinduced color change in photoluminescence? A dye/acid complex containing the same photoemissive compound was prepared. The luminophore showed both blue and red shifts in photoluminescence spectra when combined with different acids by grinding, revealing that the aggregation structure plays an important role for the mechanoresponsive behavior rather than the π‐conjugated structure.